Analysis of the Role of Digital Business Communication with Live Streaming Features in Shaping Consumer Attitudes, Interests and Trust - Herlina, Herlina; Wilujeng, Fuji Rahayu (Formosa Journal of Applied Sciences, 2024)
Live streaming communication is real-time online communication through comments, emojis and videos. The aim of the research is to determine public perceptions about the role of live streaming digital business communication in shaping consumer attitudes, interests and beliefs. Descriptive quantitative and qualitative phenomenological research methods. The research results concluded that live streaming digital business communication is able to increase consumer attitudes, interest and confidence in shopping online because live streaming has a traditional or face-to-face communication concept, thereby reducing the risk of fraud compared to digital businesses that only rely on photos, comments and videos. Therefore, live streaming can be an effective and efficient marketing medium in explaining product information in real-time which can attract consumers to establish communication so that it can increase consumer attitudes, interest and trust.